Powiatowe centrum pomocy rodzinie w perspektywie kryzysów pieczy zastępczej. W stronę transformacji działania - Rutkowski , Jarosław (Kultura-Społeczeństwo-Edukacja, 2022)
The article indicates that in the presence of various crises of foster care, there is a confusion of the district family support center, institutions not seeing and not hearing the needs of foster families and orphanages. It is emphasized that the reconstruction of the ability to hear problems and see the complex issues of foster care, for the district aid institution to go beyond the horizon of foster care, crises requires the dialogue and the courage to act in the field of social matters. Then, in the conditions of a local community, where the dialogue is practised, the district family support center regains the ability to see and hear the matters of the wounded world. As a result, the district family support center shapes the capacity of communication activities accompanied with the development of the local community. At the same time, this shift towards district local communities inhabitants’ everyday life is expressed in active care for foster care within the framework of dialogue workshops and educational activities. Such an orientation, in a trialectic perspective, in the weave of three dimensions of space the internal micro-space of the institution, the meso-space of foster care and the macro-social space of the local community – allows the district family support center to transform its activities in the field of social affairs, and experience the recognition of the inhabitants of local communities.